Crystallization, Characterization, & Application of Hydroxyl Apatite on Hydroxyl Ethyl Cellulose in the Present of Stimulated Body Fluid Solution (SBF) - Haris, Hassanal; Jahir Hussain, Fathima Shahitha; K., Kadirgama; M. M., Yusoff (American-Eurasian Network for Scientific Information Publications(AENSI), 2015)
Background: From the experiment we discovered that the hydroxyapatite can be synthesis by the crystallization process on hydroxyethylene sponges. The sponges of hydroxyethylene was fabricated successfully. The liquid placed in the freeze dryer for the sponges formation. The sponges let the samples to have larger surface area compared when it was in liquid-solid form. The larger surface area result the larger area for the formation of crystal. At the end of the study we discovered that the crystal was successfully growth on the sponges.